Musical Expression of Sholawat Art in Multicultural Societies: A Study of Composition Forms - Yahya, Luthfi bin; Muttaqin, Moh.; Muchsin, Ibnu Amar (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2020)
This study is based on society’s reality about the diversity of musical expressions of the sholawat art which is still ongoing. Therefore, this study aims to identify, analyze, and describe the musical expressions of sholawat art that exist in society in the context of a multicultural society. This study is a qualitative descriptive study with a musicology approach as the main approach. This study used several techniques for data collection, namely interview techniques, document and documentation study techniques, and observation techniques. Furthermore, the data were analyzed using content analysis with the main musicological approach which refers to the concept of composition, harmony, song form, and presentation form. The results show that in a multicultural society, such as Indonesia, there are various kinds of musical expressions of sholawat art. If we look at musicology, the diversity of musical expressions includes several kinds of expressions, which include the variety in characterization, the variety in the scale tradition used, the mixture in the use of song lyrics, and the variety in the technique of using language in composing the lyrics.